Efectos clínicos en algunas funciones visuales y en el segmento anterior del globo ocular en consumidores de cannabis - Holguín González, Angie Daniela; Torres Zapata, Mariana; Marín Aristizabal, Michael Andrés (Universidad Antonio Nariño, 2023)
Currently there are various psychoactive substances that generate effects physiological side effects in our body, different effects can be generated ophthalmic level